درجة تطبيق التخطيط الإستراتيجي في جامعة إب من وجهة نظر العاملين فيها - العفيري، نبيل أحمد محمد (جامعة ذمار - كلية التربية, 2019)
هدف البحث إلى معرفة درجة تطبيق التخطيط الاستراتيجي في جامعة إب من وجهة نظر العاملين فيها، واستخدم البحث المنهج الوصفي المسحي، وتكونت عينة البحث من (121) فرداً، تم اختيارهم بطريقة عشوائية طبقية، واعتمد البحث على الاستبانة كأداة لجمع البيانات والمعلومات بعد التأكد من صدقها وثباتها، واستخدم الباحث البرنامج الإحصائي Spss لتحليل البيانات والمعلومات. وقد خلص البحث إلى عدد من النتائج أهمها: 1-أن التخطيط الاستراتيجي في جامعة إب يطبق بدرجة متوسطة على مستوى مجمل الأداة ومجالات:(التخطيط للتخطيط الاستراتيجي، والتحليل البيئي الاستراتيجي، وتكوين وصياغة الاستراتيجية، وتنفيذ الخطة الاستراتيجية)، بينما يطبق بدرجة ضعيفة في مجال: (الرقابة وتقييم تنفيذ الخطة الاستراتيجي). 2- لا توجد فروق ذات دلالة إحصائية عند مستوى الدلالة (α =0.05) بين استجابات أفراد عينة البحث حول درجة تطبيق التخطيط الاستراتيجي في جامعة إب على مستوى مجمل الأداة وجميع المجالات تعزى لمتغير (المركز الوظيفي، وسنوات الخبرة)، بينما توجد فروق على مستوى مجال: (تكوين وصياغة الاستراتيجية). 3- توجد فروق ذات دلالة إحصائية عند مستوى الدلالة (α =0.05) بين استجابات أفراد عينة البحث حول درجة تطبيق التخطيط الاستراتيجي في جامعة إب على مستوى مجمل الأداة وجميع المجالات تعزى لمتغير (نوع القيادة)، بينما لا توجد فروق على مستوى مجال: (التخطيط للتخطيط الاستراتيجي)، ومجال: (الرقابة وتقييم تنفيذ الخطة الاستراتيجية). وفي ضوء نتائج البحث قدم الباحث جملة من التوصيات والمقترحات لتفعيل تطبيق التخطيط الاستراتيجي في جامعة إب.
This study aimed at identifying the degree of applying the strategic planning at Ibb University from its employees' perspectives. For achieving this objective, a descriptive survey approach was administered on (121) participants who were selected randomly on the basis of the random stratified sampling. That is, a questionnaire was used, after testing its validity and reliability , to collect the required data which subsequently was analyzed statistically by using the SPSS program. On the basis of the data analysis, the study revealed a number of findings, the most significant ones were: 1. The degree of applying the strategic planning at Ibb University in general was average on all areas of the instrument, namely planning for the strategic planning, strategic environment analysis, strategy construction and statement, and strategic plan implementation. But its application on the area of supervising and evaluating the strategic plan implementation was weak. 2. There were no significant statistical differences at (α = 0.05) among the participants' responses in regard to the degree of applying the strategic planning at Ibb University in all areas in general. However, all areas were attributed to the variables of job position and years of experiences but there were significant differences in regard to the area of strategy construction and statement. 3. There were significant statistical differences at (α = 0.05) among the participants' responses in regard to the degree of applying the strategic planning at Ibb University in all areas in general. However, all areas were attributed to the type of leadership variable but there were no significant statistical differences in regard to the areas of planning for strategic planning and supervision and evaluation of implementing the strategic plan. On the basis of the findings, a number of recommendations as well as suggestions were introduced for activating the application of the strategic planning at Ibb University.
Keywords: التعليم الجامعي -- طلبة الجامعات -- التخطيط الإستراتيجي -- جامعة إب -- الموارد البشرية